Documentary film-based information media for carving art in Belayu Marga Tabanan village - Putu Satria Udyana Putra; I Putu Widya Nugraha; I Ketut Sutarwiyasa; I Nyoman Widhi Adnyana; Rizkita Ayu Mutiarani (Jurnal Scientia, 2024)
The purpose of this research is to create a documentary film about Carving Art in Belayu Marga Tabanan Village. Belayu Marga Tabanan Village has a form of carving that has its own characteristics, namely the patra punggel motif. The patra punggel motif has its own philosophy and uniqueness, there is an isen or galangal plant motif. Not many people know the characteristics of the carvings owned in the village of Belayu Marga Tabanan due to the lack of information media to introduce the characteristics of the carvings owned in the village of Belayu Marga Tabanan. Therefore, this method uses a qualitative method. Data collection was carried out by interviewing sources of carving art undagi and also making observations with the community around Belayu Marga Tabanan Village. Regarding information about the art of carving at the research site, where a design is needed, namely information media, the design is based on a documentary film. In the process of making this documentary video, several stages are also needed including the pre-production stage, at this stage explaining some of the processes of making design concepts and storylines (storyboards). The next stage is the production stage at this stage where the shooting process is carried out in a documentary video and then the editing process is carried out. At the last stage there is a post-production stage process, at this post-production stage the documentary video is immediately published on YouTube social media.